The Duty of Notaries to Maintain Deed Confidentiality in the Perspective of Professional Ethics and Positive Law - Hidayat, Andi Moh. Taufiq; Huda, Miftakhul (Dinasti Research, 2026)
The obligation of notaries to maintain the confidentiality of deeds is one of the core elements of their professional function as public officials. This duty derives not only from statutory provisions under the Law on Notary Office (UUJN) but also from professional ethics that protect the integrity of legal transactions and the privacy of the parties. However, in practice, notaries may face conflicting demands between safeguarding confidentiality and fulfilling legal obligations to provide information in judicial or administrative proceedings. This conflict creates a normative dilemma that requires further examination from the perspective of both positive law and professional ethics. This study employs a normative juridical method using statutory, conceptual, and case approaches. The statutory approach analyzes the provisions of the UUJN, the Notary Code of Ethics, and relevant laws governing confidentiality in legal services. The conceptual approach investigates the theories of legal responsibility, ethical accountability, and the principle of confidentiality as developed in professional legal doctrine. Meanwhile, the case approach examines judicial decisions in which notaries were required to disclose information or provide deed copies during litigation or law enforcement processes. These approaches aim to determine whether confidentiality is absolute or subject to lawful limitations. The research concludes that confidentiality is not an unrestricted right but a qualified duty bound by ethical standards and legal boundaries. A balance must therefore be struck between the protection of private interests and the fulfillment of justice in legal proceedings. To ensure legal certainty, a clearer regulatory mechanism is needed one that defines the scope of confidentiality, the proper procedures for request and disclosure, and the legal consequences for violations. Strengthening ethical awareness and regulatory clarity will reinforce the notary’s role as both a guardian of trust and a servant of the legal system.